Chaotic activation of developmental signalling pathways drives idiopathic pulmonary fibrosis. (18th November 2020) - Froidure, Antoine; Marchal-Duval, Emmeline; Homps-Legrand, Meline; Ghanem, Mada; Justet, Aurélien; Crestani, Bruno; Mailleux, Arnaud
Idiopathic pulmonary fibrosis (IPF) is characterised by an important remodelling of lung parenchyma. Current evidence indicates that the disease is triggered by alveolar epithelium activation following chronic lung injury, resulting in alveolar epithelial type 2 cell hyperplasia and bronchiolisation of alveoli. Signals are then delivered to fibroblasts that undergo differentiation into myofibroblasts. These changes in lung architecture require the activation of developmental pathways that are important regulators of cell transformation, growth and migration. Among others, aberrant expression of profibrotic Wnt-β-catenin, transforming growth factor-β and Sonic hedgehog pathways in IPF fibroblasts has been assessed. In the present review, we will discuss the transcriptional integration of these different pathways during IPF as compared with lung early ontogeny. We will challenge the hypothesis that aberrant transcriptional integration of these pathways might be under the control of a chaotic dynamic, meaning that a small change in baseline conditions could be sufficient to trigger fibrosis rather than repair in a chronically injured lung. Finally, we will discuss some potential opportunities for treatment, either by suppressing deleterious mechanisms or by enhancing the expression of pathways involved in lung repair. Whether developmental mechanisms are involved in repair processes induced by stem cell therapy will also be discussed. IPF is driven by a chaotic activation of developmental signalling pathways https://bit.ly/3dqGaIP